Outcome mapping: A method for tracking behavioural changes in development programs - Smutylo, T. (2005)
Outcome mapping is a methodology for planning, monitoring and evaluating development initiatives that aim to bring about social change. The process of outcome mapping helps a project team or program to be specific about the actors it targets, the changes it expects to see and the strategies it employs. Results are measured in terms of the changes in behaviour, actions or relationships that can be influenced by the team or program. The methodology is comprised of several tools, which can be adapted to different contexts. It enhances team and program understanding of change processes, improves the efficiency of achieving results and promotes realistic and accountable reporting.